"Computer, please, tell me what I have to do...": An approach to agent-aided application composition - Campo, Marcelo Ricardo (2005)
The process of starting to use any reuse technology is usually one of the most frustrating factors for novice users. For this reason, tools able to reduce the learning curve are valuable to augment the potential of the technology to rapidly build new applications. In this work, we present Hint, an environment for assisting the instantiation of Java applications based on software agents technology. Hint is built around a software agent that has the knowledge about how to use a reusable asset and, using this knowledge, is able to propose a sequence of programming activities that should be carried out in order to implement a new application satisfying the functionality the user wants to implement. The most relevant contribution of this work is the use of planning techniques to guide the execution of instantiation activities for a given technology.